2016
DOI: 10.1021/acs.analchem.6b03234
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Sugar and Heavy Water Create Tunable Intact Protein Mass Increases for Quantitative Mass Spectrometry in Any Feed and Organism

Abstract: Stable isotope labeling techniques for quantitative top-down proteomics face unique challenges. These include unpredictable mass shifts following isotope labeling, which impedes analysis of unknown proteins and complex mixtures; and exponentially greater susceptibility to incomplete isotope incorporation, manifesting as broadening of labeled intact protein peaks. Like popular bottom-up isotope labeling techniques, most top-down labeling methods are restricted to defined media/feed as well as amino acid auxotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
(101 reference statements)
0
11
0
Order By: Relevance
“…174 Compared to SILAC, this method results in a more symmetric and predictable mass shift for heavy and light peak pairs, as the percentage of 13 C (or 2 H) incorporation in a protein deviates less than the percentage of lysine or arginine. 174 Although this labeling approach provides outstanding precision and accuracy, potential overlapping of the unlabeled proteoform peaks and the heavy peaks, and software requirement for picking labeled pairs still need to be addressed for large-scale quantitation. Therefore, the more accessible label-free techniques remain appealing in top-down quantitation proteomics.…”
Section: Quantitative Top-down Proteomicsmentioning
confidence: 99%
“…174 Compared to SILAC, this method results in a more symmetric and predictable mass shift for heavy and light peak pairs, as the percentage of 13 C (or 2 H) incorporation in a protein deviates less than the percentage of lysine or arginine. 174 Although this labeling approach provides outstanding precision and accuracy, potential overlapping of the unlabeled proteoform peaks and the heavy peaks, and software requirement for picking labeled pairs still need to be addressed for large-scale quantitation. Therefore, the more accessible label-free techniques remain appealing in top-down quantitation proteomics.…”
Section: Quantitative Top-down Proteomicsmentioning
confidence: 99%
“…While the only truly absolute quantitative method, unfortunately, it is limited to cell cultures and not applicable to the vast bulk of proteomic studies that focus on tissues or biofluids [ 241 ]. Furthermore, SILAC introduces an additional shift in the isotopic envelope of the mass spectrum that may result in peak overlap which, coupled with the decreased likelihood of complete labelling as a function of increasing protein size, further complicates data analysis of larger proteins [ 242 ].…”
Section: Targeted Proteomicsmentioning
confidence: 99%
“…Combining middle-down MS and metabolic labeling would be the first technique that allows discrimination of newly synthesized proteins or PTMs while preserving the information of coexisting PTM patterns. Interestingly, a few studies demonstrated that analysis of intact proteins, namely top-down MS, can be performed when such proteins are metabolically labeled [ 32 34 ]. However, histone analysis is a whole different issue, due to their very large degree of modified forms, many of them leading to the same intact protein mass.…”
Section: Introductionmentioning
confidence: 99%